Biossorção de ibuprofeno por biomassas de bagaço de cana-de-açúcar e levedura (Saccharomyces cerevisiae) ativados quimicamente - Santos, Bruna Assis Paim dos (2020)
The increase in the consumption of drugs contributes to the release of these substances in water bodies, aggravating water pollution, a recurrent and intensified environmental problem, due to the lack of specific legislation and ineffective treatments to remove these emerging contaminants. This scenario highlights the need for further studies in search of technologies capable of mitigating the effects of the presence of drugs in aquatic environments. In this context, adsorption is a promising alternative in the removal of these compounds from water, since it is considered a cheap technology, easy to operate and efficient, used from biosorbents. Therefore, the objective of the work was to employ biomass of sugarcane bagasse and yeast (Saccharomyces cerevisiae) chemically activated to remove ibuprofen from aqueous solution by adsorption. Ibuprofen and biomass were characterized by infrared spectroscopy and thermal analysis techniques, environmental conditions interfering with the process (pH, contact time, temperature, biomass dosage and drug concentration) were evaluated, and kinetic, isothermal and thermodynamics aiming to determine the mechanisms acting in the process. The characterization of biomasses identified functional groups skilled in biosorption. The experiments determined the best conditions for adsorption: pH 2, 0.25 gL-1 of biomass dosage and 25 mg.L-1 of drug concentration for both biomasses, 20ºC for adsorption with sugarcane bagasse and 40ºC for adsorption with yeast. The kinetics indicated the pseudo-second order model as the best for both biomasses. Isotherms determined physiosorption for adsorption with sugarcane bagasse and chemisorption for yeast. Regarding the biosorptive capacity, yeast obtained greater capacity than sugarcane bagasse, being 13.39 and 7.75 mg.g-1 respectively. With that, it was verified the biomass capacity of the biomass and the viability of the practical use of these by-products.